2022
DOI: 10.1530/ec-21-0304
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation for symptomatic, non-functioning, thyroid nodules: a single-center learning curve

Abstract: Objective: Radiofrequency ablation (RFA) is increasingly considered the prime option for treating symptomatic, benign, non-functioning thyroid nodules (NFTN). However, little is known about the degree of operator experience required to achieve optimal results. This study describes the RFA learning curve of a single-centre team. Methods: Retrospective cohort study of the first 103 patients receiving RFA treatment for a single, symptomatic, and benign NFTN, with a follow-up of at least one year. Primary outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…According to a large body of evidence, demonstrating that RFA-associated complications are rather rare, the main outcome measure to determine RFA proficiency has become the rate of volume reduction ( 15 ). Thus, three previous studies have conventionally focused on a minimum threshold for procedural volume in order to achieve a higher 6-month VRR ( 7 9 ). Bom et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a large body of evidence, demonstrating that RFA-associated complications are rather rare, the main outcome measure to determine RFA proficiency has become the rate of volume reduction ( 15 ). Thus, three previous studies have conventionally focused on a minimum threshold for procedural volume in order to achieve a higher 6-month VRR ( 7 9 ). Bom et al.…”
Section: Discussionmentioning
confidence: 99%
“…Bom et al. demonstrated that about 40 procedures are required to achieve a VRR >50% and of 79% in the following 63 patients ( 9 ). Russ et al, in their experience with the first 90 patients treated, showed that a LC existed regarding technical efficacy, VRR, and ablation ratio, a relatively new objective parameter to assess the percentage of the successfully ablated nodule.…”
Section: Discussionmentioning
confidence: 99%
“…Its pathogenesis is diffuse thyroid hyperplasia and enlargement caused by long-term iodine deficiency, and long-term proliferative and degenerative lesions alternate repeatedly, leading to nodules. However, in a small number of cases, nodule regrowth is caused by an underlying malignant tumor 13 . Li et al 14 reported that RFA had a low effective rate in the treatment in children, with a volume reduction rate (VPR) of 77.5% and a nodule regeneration rate of 22.9% at 12 months after operation.…”
Section: Discussionmentioning
confidence: 99%
“…해당 연구는 고주파 절제술을 시행한 102명의 환자를 대상으로 하였고 치료된 결절의 VRR은 치료를 받은 순서대로 점진적으로 증가하였으며, 이를 바탕으로 저자들은 고주파 절제술에 대한 학습 곡선을 다음과 같이 3단계로 구성하여 제시하였다; 초기 학습 단계(20건 이하), 기술 통합 단계(21–65건), 숙련 단계(65건 초과). Bom 등( 21 )에 의한 가장 최근 연구는 103명의 단일 시술을 받은 환자에서 학습 곡선을 분석하였으며 앞선 연구들과 비슷하게 시술자가 40건의 시술 후 75%의 환자에서 6개월 후 VRR이 50% 이상에 도달하는 결과를 보였다고 보고하였다.…”
Section: 갑상선 고주파 절제술 교육의 현재unclassified